(untitled) (Researcher CAB: A Journal for Research and Development, 2023)
Today entrepreneurial intention is considered one of the most eminent drivers for the overall escalation of the nation’s economic growth. This study examines the relationship between financial literacy, saving behaviour, family financial socialization and entrepreneurial intention among individuals. Further, this paper also investigates how family financial socialization moderate the relationship between these factors and entrepreneurial intention. The study followed the positivist research philosophy. The deductive approach, quantitative research method, and explanatory research design have been applied. Data were collected from 415 university-level business students of Karnali Province using a purposive sampling technique. The hypotheses were tested through the structural equation modelling technique. The study found the significant positive relationship between financial literacy, saving behaviour and family financial socialization with entrepreneurial intentions. Family financial socialization moderates the relationship between financial literacy, saving behaviour and entrepreneurial intention. The findings of this study can be implemented by policymakers, educators, and other stakeholders to promote financial literacy and saving behaviour to develop effective strategies for enhancing entrepreneurial intention among individuals.